Using literature to improve the moral imagination - Stephen Kekoa Miller (Journal of Philosophy in Schools)
The primary aim of this essay will be to look at a few arguments for how to improve Moral Imagination. Next, it will discuss how ‘stories’ and ‘pretending’ can alter how we think and act. Additionally, one underdeveloped aspect of traditional normative ethics involves how Moral Imagination is employed but usually not overtly discussed. Finally, the essay will offer an argument for how to use narrative fiction in a philosophy classroom to deepen these abilities.